Structural and iron content changes in subcortical vascular mild cognitive impairment: a combined voxel-based morphometry and quantitative susceptibility mapping study - Yushuang Liu; Yingqi Lu; Liyu Hu; Jinping Xu; Xingchen Liu; Nan Yang; Shangjie Chen; Zhongling Zhang (Brain Research Bulletin)
Background: Further studies are necessary to investigate the neural mechanisms elemental of subcortical vascular mild cognitive impairment (svMCI), which is considered as precursor to vascular dementia (VaD). This objective of this research was to investigate the alterations in gray matter volume and brain iron deposition in patients with svMCI. Methods: This study involved 23 patients classified as health controls (HC) and 20 patients diagnosed with svMCI. All participants received cognitive assessments and magnetic resonance imaging (MRI). This research contains voxel-based morphometry (VBM), voxel-based quantitative susceptibility mapping (QSM) analysis, ROI-based QSM analysis, and correlation analysis. Results: svMCI patients showed more seriously cognitive impairment than HC patients. VBM analyses showed gray matter atrophy in the cingulate gyrus in the svMCI. Voxel-based QSM analyses showed increased susceptibilities in the right middle frontal gyrus, left paracentral lobule, as well as decreased susceptibility in the right postcentral gyrus in the svMCI. And ROI-based QSM analyses showed increased susceptibilities in left caudate nucleus and cerebellum in the svMCI. In addition, the susceptibility in left middle cingulate cortex and paracingulate gyrus was positively correlated associated with MoCA scores (r = 0.538 p < 0.001), and the susceptibility in the right middle frontal gyrus was negatively correlated with MoCA scores (r = -0.418 p < 0.007). Conclusions: The results of our studies suggest that morphological alterations and iron burden in the brain may be related to cognitive dysfunction in svMCI patients, providing a new way to explore underlying neural mechanisms of cognitive dysfunction.